Production of light flavour hadrons at intermediate and high pT in pp, p-Pb and Pb-Pb collisions measured with ALICE - Knichel, Michael Linus (Nuclear physics. A, Nuclear and hadronic physics, 2014)
Light flavour transverse momentum spectra at intermediate and high pT provide an important baseline for the measurement of perturbative QCD processes in pp, for the evaluation of initial state effects in p-Pb, and for investigating the suppression from parton energy loss in Pb-Pb collisions. The measurement of the nuclear modification factor RpPb for inclusive charged particles is extended up to 50 GeV/c in pT compared to our previous measurement and remains consistent with unity up the largest momenta. Results on RpPb of charged pions, kaons and protons that cover up to 14 GeV/c in pT are presented and compared to RpPb of inclusive charged particles. On the production of charged pions, kaons, and protons up to pT=20 GeV/c in Pb-Pb collisions final results for RAA are presented.
Gesehen am 08.12.2020
Im Titel ist "T" bei high pT tiefgestellt